Reengineering the Educational System of Farhangian University: A Grounded Theory Approach - Houshiarjah, Nazanin; Shariatmadari, Mehdi; Kordestani, Fereshteh; Hamidifar, Fatemeh (Iranian Journal of Educational Sociology, 2026)
Purpose: This study aimed to develop a comprehensive model for reengineering the educational system of Farhangian University in Tehran based on the grounded theory approach to improve teacher education quality and institutional effectiveness. Methods and Materials: The research employed a qualitative design using the paradigmatic grounded theory method of Strauss and Corbin (1998). Twenty academic experts and specialists in higher education, educational management, curriculum design, and teacher training were selected through theoretical sampling until theoretical saturation was achieved. Data were collected via semi-structured, in-depth, exploratory interviews complemented by documentary analysis. Data validity and reliability were ensured through prolonged engagement, triangulation, peer debriefing, and member checking. Coding was conducted in three stages—open, axial, and selective—using MAXQDA software to extract key dimensions, causal relationships, and strategies forming the systemic model of educational reengineering. Findings: The analysis revealed that reengineering the educational system is a multifaceted process shaped by infrastructural–technological, organizational, human, cultural, and social factors. Causal conditions included outdated curricula, limited technological adaptation, and rigid administrative structures. Contextual factors encompassed political and ideological barriers and inadequate infrastructure, while motivational–psychological and economic elements acted as intervening variables. Effective strategies involved communication and collaboration networks, human resource development, instructional redesign, and managerial innovation. The identified outcomes included enhanced teaching quality, a positive and motivational learning environment, alignment with societal and labor market needs, and strengthened institutional credibility. Conclusion: Reengineering the educational system of Farhangian University requires an integrated, systemic approach addressing structural, cultural, and technological dimensions. By combining collaborative strategies with digital transformation and human capital development, universities can foster innovation, efficiency, and educational excellence aligned with contemporary national and global demands.